Management Techniques for Organizational Rumor and Gossip in Schools - Bünyamin HAN (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This research aims to determine the techniques for effective management of organizational rumor and gossip in schools. Rumors are informal conversations circulating among the employees of the organization towards an event. Gossips are informal evaluative speech about people who are not present there. Rumors and gossips are common informal conversations, which should be managed by school administration. In this term, this research investigates the ways of managing them. The study is a phenomenological qualitative research carried out by conducting semi-structured interviews with 33 teachers in Diyarbakır, Turkey. The data were analyzed by using content analysis technique and some themes and categories were created. According to the research results, school administration should organize some informative seminars on awareness, communication and values in order to reduce the harmful aspects of rumor and gossip. The school administration should adopt a transparent management approach, establish a feedback mechanism, provide effective communication, operate formal communication channels and react to those who spread harmful rumor and gossip. The rumors and gossips can be used for organizational purposes such as; improving intimate relationships, recognizing the organization and employees, improving group cooperation and sincerity, understanding the hidden side of events, learning innovations and changes, learning how changes and practices are perceived, identifying deficiencies and problems in jobs, learning employee expectations.